2003
DOI: 10.1542/peds.112.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Thimerosal and the Occurrence of Autism: Negative Ecological Evidence From Danish Population-Based Data

Abstract: The discontinuation of thimerosal-containing vaccines in Denmark in 1992 was followed by an increase in the incidence of autism. Our ecological data do not support a correlation between thimerosal-containing vaccines and the incidence of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
3
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(98 citation statements)
references
References 9 publications
4
82
3
9
Order By: Relevance
“…But the prevalence of NDs has continued to increase (Fombonne et al, Madsen KM et al,) even with the use of thimerosal free vaccines after the joint statement regarding thimerosal use in 1999, as must have been expected according to the results of these studies. 16,38 This observation diminishes the likelihood of any association of an increase in neurological abnormalities in children with exposure to thimerosal.…”
Section: Study Findings Conducted Bymentioning
confidence: 99%
“…But the prevalence of NDs has continued to increase (Fombonne et al, Madsen KM et al,) even with the use of thimerosal free vaccines after the joint statement regarding thimerosal use in 1999, as must have been expected according to the results of these studies. 16,38 This observation diminishes the likelihood of any association of an increase in neurological abnormalities in children with exposure to thimerosal.…”
Section: Study Findings Conducted Bymentioning
confidence: 99%
“…Autism Autism is exhibited in the lack of ability to form relationship and behave normally in young children of less than three years old. The ability of chemicals to possibly play a role in disrupting retinoids during the time of neural tube closure in the womb was posited by Madsen et al (2003) or rather a difference in metabolism could be the cause (Charman, 2002). Nonetheless, the important thing is what triggers the disorder and it is clear that an environmental factor is responsible (Stern and Smith, 2003) in addition to chemicals as the most likely candidates.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…This severely biased the dataset, and it should not have been used to assign causality. Meanwhile, several other studies performed by various groups of researchers did not support the postulated association between thimerosal and ASDs [33,[105][106][107][108][109][110][111][112]. Three ecological studies were performed in 3 different countries comparing the incidence of autism with thimerosal exposure from vaccines [33,109,110].…”
Section: Insufficient Scientific Evidence Linking Thimerosal With Autismmentioning
confidence: 99%
“…In each case, thimerosal had been removed from childhood vaccines, allowing robust comparisons of vaccination with thimerosal-containing and thimerosal-free products. A large study from Denmark showed no difference in the incidence of autism among children who had received vaccines containing different amounts of thimerosal [109]. Despite the removal of thimerosal from vaccines in 1992 in Sweden and Denmark, the incidence of autism increased steadily from 1990 to 2000 [110].…”
Section: Insufficient Scientific Evidence Linking Thimerosal With Autismmentioning
confidence: 99%